???? ??????? ???????? ?? ????? ??????? - Damhuri Damhuri; Ratni Bt. H. Bahri (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2018)
Human beings are created by God into two big clustersnamely male and female. Based on striking differences between the two types of creatures has implications for many things, including language..The grouping of nouns by type is a fairly unique phenomenon. The phenomenon is found almost in most languages ??of the world, not only in the Smith-Hmit family, but in Indo-European languages ??with varying quality and quantity.In Arabic, the example of this linguistic phenomenon is very powerful and is one of the characteristics of the Arabic language.The most popular theory of word grouping into muzakkar (male) and muannats (females) is a theory that sees a connection and relationship between the word(lafaz) and the meaning (Makna). In the historical perspective of ancient society, it is also associated with the myths of public belief based on the nature of the world in general consists of muzakkar and muannats.These theory - in another perspective - especially the ancient society has the power of argument and reason, but in the perspective of modern society has a deadlock of argument and loses its relevance. The issue not only ends in the classification aspect, but it is more difficult to make perfect rules that can be followed to identify the types of muzakkar and muannats. The rules of muzakkar and muannats in the reference books of nahwu are not separated from a large number of exceptions. Therefore, the conclusion of the muzakkar and muannats theories in Arabic refers to the tradition of Arabic usage of a particular word, and empowering a complete encyclopedia of muzakkar and muannats rather than creating many rules that are unable to accommodate a general distinction between the two type of the word.